PERBANDINGAN BERAT BADAN, TINGGI BADAN, DAN LINGKAR KEPALA ANAK KARIES RAMPAN USIA 2-5 TAHUN DENGAN STANDARD ANTROPOMETRI WHO-NCHS 2005 DI PAUD AL-AZHAR KOTA BANDA ACEH - Dharli Syafriza; Herwanda Herwanda; Arinal Haqqa; Refasari Ifani; Elvida Muliana (Journal of Syiah Kuala Dentistry Society, 2016)
Rampant caries is the most common infectious disease of childhood, defined as caries that suddenly appears and widespread resulting in early pulp involvement, and affect teeth surfaces which are generally immune to caries; mandibular insicors and canines. Dental pain and infections in children can caused eating difficulty which influence nutritions intake so affect growth and development. This study aims to compare body weigth, body heigth, and head circumference of 2-5 years old rampant caries children with WHO-NCHS 2005 anthropometry standard. Subjects aged 2-5 years old were children in PAUD Al-Azhar Kota Banda Aceh. Result showed a significant differences between body weigth, body heigth, and head circumference of 2-5 years old rampant caries children with WHO-NCHS 2005 anthropometry standard in PAUD Al-Azhar Kota Banda Aceh (p0,05). Body weigth, body heigth, and head circumferences of rampant caries children were lower than WHO-NCHS 2005 anthropometry standard.Keyword: Rampant Caries, Body Weight, Body Heigth, Head Circumferences, WHO-NCHS 2005 Anthropometry Standard